Greener Selective Cycloalkane Oxidations with Hydrogen Peroxide Catalyzed by Copper-5-(4-pyridyl)tetrazolate Metal-Organic Frameworks - Martins, Luisa (2016)
Microwave assisted synthesis of the Cu(I) compound [Cu(µ4-4-ptz)]n [1, 4-ptz = 5-(4-pyridyl)tetrazolate] has been performed by employing a relatively easy method and within a shorter period of time compared to its sister compounds. The syntheses of the Cu(II) compounds [Cu3(µ3-4-ptz)4(µ2-N3)2(DMF)2]n∙(DMF)2n (2) and [Cu(µ2-4-ptz)2(H2O)2]n (3) using a similar method were reported previously by us. MOFs 1-3 revealed high catalytic activity toward oxidation of cyclic alkanes (cyclopentane, -hexane and -octane) with aqueous hydrogen peroxide, under very mild conditions (at room temperature), without any added solvent or additive. The most efficient system (2/H2O2) showed, for the oxidation of cyclohexane, a turnover number (TON) of 396 (TOF of 40 h−1), with an overall product yield (cyclohexanol and cyclohexanone) of 40% relative to the substrate. Moreover, the heterogeneous catalytic systems 1–3 allowed an easy catalyst recovery and reuse, at least for four consecutive cycles, maintaining ca. 90% of the initial high activity and concomitant high selectivity.